Analysis of the Factors Influencing the Implementation of Child-Friendly City Policy in Situbondo Regency (Regional Regulation Number 6 of 2020) - Ishar Rizki Milian; Edy Wahyudi .; Hadi Prayitno . (Jurnal Ad'ministrare, 2023)
As a gift from God Almighty, children must always be protected and cared by the State for their basic rights for survival, growth, development and protection from violence and violations. To guarantee these, Situbondo Regency Government has established Regional Regulation number 6 of 2020 concerning the Implementation of Child-Friendly City in Situbondo Regency. In fact, based on data from the education cluster in 2021, the number of dropouts was 2066 students, or increased ± 2000% from the previous year. Meanwhile, from the family and alternative care cluster, the number of dispensation requests for marriage in the last two years increased by ± 500%. This research aimed to analyze the implementation of child-friendly city policy applying five clusters. Using descriptive-qualitative method, data were collected interactively. The results showed that factors affecting the success of policy implementation such as disposition, resource, communication, bureaucratic structure, and environment were still unsatisfying, indicated by the high number of children dropping out of school, high demand for marriage dispensation, and nonoptimal job descriptions and evaluation. Thus, to achieve the child-friendly city, extraordinary efforts are needed in cultivating the mindset that children care is national affairs due to the fate of the nation's future generation